Personalisasi Media Netflix Dalam Kehidupan Remaja Kota Makassar - Muhammadia, A.Adelia Hardianti; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Nowadays, online streaming services are becoming a favorite choice for the public, especially teenagers, to look for entertainment in the form of films or series. In this study, the author has the view that teenagers have their own motives and needs in subscribing to and consuming film series on Netflix. This is helped by Netflix's personalization, which provides recommendations for various viewing options that allow users to find the content to watch that they enjoy. This research uses descriptive-explanative research with a qualitative approach to explore the motives and influence of Netflix on the lives of teenagers in Makassar City using uses and gratification theory analysis. The results of this research indicate that Netflix media personalization is could to make it easier for users to get various shows and is able to trap teenagers to fulfill various motives of need in terms of productive and pseudo-needs fulfillment. Keywords: Netflix, personalization, lives of teenegers.